PSYCHOLOGICAL EXPERIENCE OF POST-TRAUMATIC GROWTH IN ADULTS AS A RESULT OF ADOLESCENT BULLYING VICTIMIZATION - Yaisarmer, Supawan; Areekit, Poonsub; Taephant, Nattasuda (Academic Psychiatry and Psychology Journal, 2024)
Objective: This qualitative research proposed to study the psychological experience of post-traumatic growth in adults as a result of adolescent bullying victimization Method: This qualitative research used Interpretative Phenomenological Analysis (IPA). Six key informants were individuals who self-reported as victims of bullying in adolescence and had experienced post-traumatic growth as a result of being bullied in at least 1 of 5 domains of post-traumatic growth. Semi-structured in-depth interviews were employed between March to September 2023 Results: Data analysis resulted in four superordinate themes: (1) Seismic world from being bullied, which represents perceptions of self and others of individuals challenged by being bullied and trying to continue surviving and living with the negative effects of these traumatic experiences; (2) Cultivating process for post-traumatic growth, which is contributed by experiencing and developing internal and external processes of self-to-self and self-to-other perceptions during and after being bullied, accordingly, leads to the acceptance process; (3) Post-traumatic growth as a result of being bullied, the positive changes after trying to survive and cope with distress from being bullied, which are self-assured, being secure in a relationship, motivation to self-development, and appreciation of life; and (4) Developed skills through this life experience referring to expanded psychological coping skills, developed social skills, and compassion for others which individuals developed by going through experiences of being bullied and coping with its negative effects over time. Conclusion: Being bullied during adolescence might be a traumatic experience, challenged key informants' perceptions of self-to-self and self-to-others, in which negative intrusive thoughts toward self and others occurred. However, engaging in self-introspective processes and receiving support from others facilitate the acceptance of oneself, and past experiences. Such processes serve as a foundation for post-traumatic growth.